2006
DOI: 10.1159/000094443
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Bcl-2 and Ki-67 in Tamoxifen-Associated Endometrial Polyps: Comparison with Postmenopausal Polyps

Abstract: Background: The aim of this study was to evaluate the expression of Bcl-2 and Ki-67 in tamoxifen (TAM)-associated endometrial polyps and postmenopausal polyps. Material and Methods: For this purpose, a retrospective analysis of paraffin-embedded specimens was carried out. Polyps of 20 postmenopausal and 14 TAM-treated patients, 11 simple endometrial hyperplasia, 10 atypical complex endometrial hyperplasia and 8 endometrial adenocarcinoma specimens were included in the study. Hematoxylin/eosin-stained sections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
(36 reference statements)
0
5
0
1
Order By: Relevance
“…17 Other studies have similarly observed that there is decreased apoptosis in endometrial polyp tissue. [18][19][20] Glandular, menopauseindependent AB DNA fragmentation factor 40, 45 (DFF40), (DFF45) and Bcl-2 overexpression may play an important role in the pathogenesis of endometrial polyps. 21 Ki67 expression was observed to occur predominately in the proliferative phase, with glandular epithelium exhibiting the strongest expression.…”
Section: Aetiology and Pathogenesismentioning
confidence: 99%
“…17 Other studies have similarly observed that there is decreased apoptosis in endometrial polyp tissue. [18][19][20] Glandular, menopauseindependent AB DNA fragmentation factor 40, 45 (DFF40), (DFF45) and Bcl-2 overexpression may play an important role in the pathogenesis of endometrial polyps. 21 Ki67 expression was observed to occur predominately in the proliferative phase, with glandular epithelium exhibiting the strongest expression.…”
Section: Aetiology and Pathogenesismentioning
confidence: 99%
“…Bcl-2 expression is higher in the endometrium of PCOS patients than in a control group. Bcl-2 expression also forms more heterodimers by binding to BAX to inhibit the apoptosis of PCOS endometrial cells (Altaner et al, 2006;Tao et al, 1997). During a regular menstrual cycle, Bcl-2 expression is regulated by sex hormones.…”
Section: Tablementioning
confidence: 99%
“…There is patchy condensation of the stromal cells around the glands. It has been reported that Bcl-2 and Ki-67 expression was higher in tamoxifen-associated polyps than in postmenopausal untreated polyps (Altaner et al 2006). These findings suggest that tamoxifen-associated endometrial polyps have higher rates of cell mitotic activity and apoptosis inhibition; these higher rates may play a crucial role in the malignant transformation of such endometrial polyps.…”
Section: Uterine Corpusmentioning
confidence: 99%